AC electric motors control : advanced design techniques and applications - Giri, Fouad (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
The complexity of AC motor control lies in the multivariable and nonlinear nature of AC machine dynamics. Recent advancements in control theory now make it possible to deal with long-standing problems in AC motors control. This text expertly draws on these developments to apply a wide range of model-based control designmethods to a variety of AC motors. Contributions from over thirty top researchers explain how modern control design methods can be used to achieve tight speed regulation, optimal energetic efficiency, and operation reliability and safety, by considering online state var.
pt. 1. Control models for AC motors -- pt. 2. Observer design techniques for AC motors -- pt. 3. Control design techniques for induction motors -- pt. 4. Control design techniques for synchronous motors -- pt. 5. Industrial applications of AC motors control.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Electric motors, Alternating current -- Automatic control; SCIENCE / System Theory; Electric motors, Alternating current -- Automatic control; Control theory; Electric motors, Alternating current -- Automatic control; Machine dynamics; Science -- System control; Electronic books; Electronic books; Electronic books